2004
DOI: 10.1111/j.1365-2710.2004.00571.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective drug utilization evaluation of vancomycin usage in paediatric patients

Abstract: The majority of dosing regimens of vancomycin was consistent with guideline criteria. The most evident problem was the sub-optimal use of the monitoring of vancomycin serum levels. The information derived from this study may be used as a for further study and for the development of strategies for optimize vancomycin usage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…Although vancomycin is one of the commonly used medications in critically ill pediatric patients (5), there are no benchmark criteria for vancomycin utilization in pediatric patients. Most of the reports on vancomycin use are confined to appropriateness of vancomycin prescription (12)(13)(14), indications (15), and percent of population (5, 16) who received vancomycin. Vancomycin use density per unit patient days has not been systematically studied.…”
Section: Discussionmentioning
confidence: 98%
“…Although vancomycin is one of the commonly used medications in critically ill pediatric patients (5), there are no benchmark criteria for vancomycin utilization in pediatric patients. Most of the reports on vancomycin use are confined to appropriateness of vancomycin prescription (12)(13)(14), indications (15), and percent of population (5, 16) who received vancomycin. Vancomycin use density per unit patient days has not been systematically studied.…”
Section: Discussionmentioning
confidence: 98%
“…It should be noted that many of the neutropenia-type reactions in patients studied in this research were excluded as ADRs because patients were also using antineoplastic drugs that may more frequently lead to the development of this ADR [8], however case reports have increased [3,7] and greater attention has been given to this ADR. In a retrospective study with pediatric patients [25], thrombocytopenia corresponded to 26.3% of ADRs, and was the second most prevalent ADR to vancomycin in that study. More recently, the incidence of this ADR was studied by monitoring patients treated with vancomycin over a five year period and this corroborated the results reported in the present study [26].…”
Section: Resultsmentioning
confidence: 97%
“…This is higher than Retrospective drug utilization evaluation in pediatric patients in USA showed that large percentages (30%-50%) of antibiotics administered in the USA are given to prevent infection rather than to treat established disease. This practice accounts for some of the most fragment misuses of these drugs [20]. This could be due to difference in advancement in health service delivery system like advanced laboratories for diagnosis of definitive pathogens to target and expertise on antibiotics like infectious disease specialists which are at very young stage in study area.…”
Section: Discussionmentioning
confidence: 99%
“…Most frequently prescribed antibiotics to children were Ampicillin, Chloramphenicol and Gentamicin [19]. Retrospective drug utilization evaluation in pediatric patients in USA showed that large percentages (30%-50%) of antibiotics administered in the USA are given to prevent infection rather than to treat established disease [20].…”
Section: Introductionmentioning
confidence: 99%